Search Costs and Equilibrium Price Dispersion in Auction Markets - Matthew R. Backus; Joseph Uri Podwol; Henry S. Schneider (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2013)
A leading explanation for price dispersion in posted-price markets is search costs. We incorporate this insight into a model of competing second-price auctions similar to eBay. By doing so, we extend the narrow literature on competing auctions to capture price dispersion, and grow the already vast literature on price dispersion to include auctions. We provide evidence for the model using data collected from eBay, identifying search costs by exploiting a discontinuity in the visibility of auctions due to eBay's search tool.
Keywords: 330